Body surface area measurement for lesion area assessment - Hani, A.F.M. (CRC Press, 2014)
Psoriasis is one of the most common skin disorders. The disease appears as red scaling plaques that can spread on any body part 1. In psoriasis, the immune system sends incorrect signals that speed up the growth of new skin cells. Psoriasis affects about 2%-3% of the worldâs population 2, 3. The Dermatological Society of Malaysia estimates the prevalence of psoriasis in Malaysia to be 3% 4. Since the disease cannot be totally cured, a psoriasis patient needs continuous and long-term treatment. The Psoriasis Area and Severity Index (PASI) scoring method is the gold standard for severity assessment and in determining treatment efficacy 5. Four parameters-area (ratio of lesion area to total body surface area), erythema, scaliness, and thickness-are examined to determine the PASI score. The parameter scores from each body region (head, trunk, upper limbs, and lower limbs) are weighted and totaled to provide a PASI score ranging from 0 to 72. Â© 2014 by Taylor & Francis Group, LLC.